2014
DOI: 10.4103/0973-1296.139807
|View full text |Cite
|
Sign up to set email alerts
|

A new mulinane diterpenoid from the cushion shrub Azorella compacta growing in Perú

Abstract: Background:Azorella compacta is a rare yellow-green compact resinous cushion shrub growing from the high Andes of southern Perú to northwestern Argentina, and which is a producer of biologically active and unique diterpenoids.Objective:This study investigated the secondary metabolites present in a Peruvian sample of Azorella compacta and the evaluation of gastroprotective activity of the isolated compounds in a gastric- induced ulcer model in mice.Material and Methods:Six secondary metabolites (diterpenoids 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…The same study demonstrated that the mulinane diterpenoids have increased the activity due to the presence of an additional carboxylic acid [32]. In another study, the hydro-carbonated compounds mulin-11,13-diene, mulin-11,13-dien-20-ol, and mulin-11,13-dien-20-oic acid were less active than lansoprazole reducing the gastric lesions by 18%, 26% and 39%, respectively [32,33]. Regarding the mode of gastroprotective action for mulin-11,13-dien-20-oic acid evaluated at 55 mg/kg, its effect was reduced by pre-treatment with indomethacin and N -ethylmaleimide, suggesting that prostaglandins and sulfhydryl compounds are positively involved in the gastroprotective activity of this mulinane diterpenoid [11].…”
Section: Resultsmentioning
confidence: 99%
“…The same study demonstrated that the mulinane diterpenoids have increased the activity due to the presence of an additional carboxylic acid [32]. In another study, the hydro-carbonated compounds mulin-11,13-diene, mulin-11,13-dien-20-ol, and mulin-11,13-dien-20-oic acid were less active than lansoprazole reducing the gastric lesions by 18%, 26% and 39%, respectively [32,33]. Regarding the mode of gastroprotective action for mulin-11,13-dien-20-oic acid evaluated at 55 mg/kg, its effect was reduced by pre-treatment with indomethacin and N -ethylmaleimide, suggesting that prostaglandins and sulfhydryl compounds are positively involved in the gastroprotective activity of this mulinane diterpenoid [11].…”
Section: Resultsmentioning
confidence: 99%
“…A. absinthium contiene metabolitos secundarios (e.g. terpenoides, fenilpropanoides, timol y eugenol) con propiedades antihelmínticas, antibacteriales y antiprotozoarios (Hussain et al, 2017), B. tricuneata tiene terpenos (nerolidol) con efectos bactericidas y fungicidas (Abad y Bermejo, 2007), A. compacta contiene diterpenoides con propiedades acaricidas (Salgado et al, 2014;Tello et al, 2014) y antiplasmódicas (Loyola et al, 2004). Respecto a L. daucifolia aún no se ha caracterizado sus metabolitos secundarios, a pesar de su amplio uso para el control de la sarna y parasitosis entérica.…”
Section: Discussionunclassified
“…A number of azorellanes ( 9 , 11 , and 15 ) and mulinanes ( 1 , 5 , 6 , 28 , 29 , 31 , and 40 ) isolated from A. compacta exhibited gastroprotective activity in HCl/EtOH-induced gastric lesions in mice, at a dose of 20 mg/kg. The best activity was caused by mulin-11,13-dien-18-acetoxy-16,20-dioic acid ( 31 ), azorellanol ( 9 ), and 13 β -hydroxyazorellane ( 15 ), with values (73–69%) similar to those observed for the positive control Lansoprazole (78–68%) at the same dose [ 24 , 26 ]. Similarly, mulin-11,13-dien-20-oic acid ( 6 ) isolated from A. trifurcata also demonstrated a gastroprotective effect (ED 50 = 55 mg/kg); the possible mode or gastroprotective action of 6 was evaluated in mice using a pre-treatment with various blockers such as Indomethacin (inhibitor of prostaglandin synthesis), N-ethylmaleimide (blocker of sulfhydryl compounds), N-nitro-L-arginine methyl ester (inhibitor of nitric oxide), and ruthenium red (vanilloid receptor antagonist).…”
Section: Pharmacological Activities Of Mulinane and Azorellane Ditmentioning
confidence: 90%